A highly selective and sensitive chemiluminescent probe for leucine aminopeptidase detection in vitro, in vivo and in human liver cancer tissue. Issue 8 (7th February 2022) - Wang, Baoqu; Chen, Zhenzhou; Cen, Xiaohong; Liang, Yuqing; Tan, Liyi; Liang, En; Zheng, Lu; Zheng, Yanjun; Zhan, Zhikun; Cheng, Kui
Abstract : The first chemiluminescent probe for the detection of LAP is described. It shows a highly selective, sensitive and rapid chemiluminescence response for the detection of LAP in vitro and in vivo, and enables the differentiation of liver cancer. Abstract : Leucine aminopeptidase (LAP) is involved in tumor cell proliferation, invasion, and angiogenesis, and is a well-known tumor marker. In recent years, chemiluminescence has been widely used in the field of biological imaging, due to it resulting in a high sensitivity and excellent signal-to-noise ratio. Here, we report the design, synthesis, and evaluation of the first LAP-activated chemiluminescent probe for LAP detection and imaging. The probe initially had no chemiluminescence but produced an extremely strong chemiluminescence after the release of the dioxetane intermediate in the presence of LAP. The probe had high selectivity over other proteases and higher signal-to-noise ratios than commercial fluorophores. Real-time imaging results indicated that the chemiluminescence was remarkably enhanced at the mice tumor site after the probe was injected. Furthermore, the chemiluminescence of this probe in the cancerous tissues of patients was obviously improved compared to that of normal tissues. Taken together, this study has developed the first LAP-activable chemiluminescent probe, which could be potentially used in protein detection, disease diagnosis, and drug development.